1997
DOI: 10.1063/1.593396
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity effects in hopping conductivity of La2CuO4 single crystal with excess oxygen

Abstract: The hopping conductivity of La2CuO4+δ single crystal with excess oxygen has been studied. It is found that the transition from variable-range hopping (with the temperature dependence of resistance R∝exp(T0/T)1/4) to simple activation conductivity (R∝exp(Δ/kT)) occurs at a temperature lower than 20 K. This transition is accompanied with significant changes in the behavior of magnetoresistance and current–voltage characteristics. It is shown that such a behavior of hopping conductivity below 20 K is due to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 2 publications
3
11
0
Order By: Relevance
“…In Ref. [14,15] it was found that the transition from VRH to simple activation conduction [R ∝ exp(∆/kT )] occurs at temperatures below 20 K (the similar effect was described also before in Ref. [13]).…”
Section: Introductionsupporting
confidence: 70%
“…In Ref. [14,15] it was found that the transition from VRH to simple activation conduction [R ∝ exp(∆/kT )] occurs at temperatures below 20 K (the similar effect was described also before in Ref. [13]).…”
Section: Introductionsupporting
confidence: 70%
“…3). In previous studies, negative MR in the AF La 2 CuO 4+δ for the case of both the current and field parallel to CuO 2 was found and discussed to a certain degree [14,18]. The nature of the negative MR in rather low field H c and J a,b revealed in this work is not clear and is worthy of additional study.…”
Section: Resultsmentioning
confidence: 69%
“…In Ref. [14], a possible reason for this behavior is suggested to be determined by the presence of superconducting inclusions in insulating sample due to phase separation in La 2 CuO 4+δ .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations